Perilaku Manajer Atas Isu Manajemen Lingkungan Terhadap Kinerja Keuangan Dengan Menggunakan Variabel Intervening Customer Satisfaction Pada Perusahaan Di Surabaya - Daniela, Stephanie Anne (Business Accounting Review, 2016)
This study aims to examine the influence of the attitude of managers on the issue of environmental management towards the companys financial performance, with Customer Satisfaction as intervening variable. Manager attitude on Environmental Management Issues was used as independent variables. Financial performance used primary data as the dependent variable. This study also used Customerâs Satisfaction as intervening variable.. The sample used in this study was manufacturing and non-manufacturing firms in Surabaya. This study used quantitative approach, and the data obtained through the distribution of questionnaires. The hypothesis was tested by path analysis modeling techniques with SmartPLS. The results from this study showed that there was a significant and positive influence on Manager Attitude on Environmental Management Issues to financial performance, manager attitude on environmental management issues to financial performance, and customerâs satisfaction to financial performance on manufacturing and non-manufacturing firms in Surabaya.